Green Biginelli‐type Reaction: Solvent‐free Synthesis of 5‐unsubstituted 3, 4‐dihydropyrimdin‐2(1H)‐ones. (4th November 2014) - Wang, Min; Song, Jilei; Lu, Qilin; Wang, Qinglin
Abstract : The Biginelli‐type compounds, 5‐unsubstituted 3, 4‐dihydropyrimdin‐2(1 H )‐ones were synthesized by a one‐pot three‐component condensation of aromatic aldehydes, aromatic ketones and urea in the presence of SnCl4  · 5H2 O under solvent‐free conditions. The advantages of this method are short reaction time (4–10 min), excellent yields (74–97%), inexpensive catalyst and solvent‐free conditions. A plausible mechanism was proposed. Abstract :